Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode, preparation method thereof and detection method of uric acid
By using Py-PB-COF/glass carbon microsphere-ionic liquid paste electrode, the existing electrodes have poor reproducibility and complex preparation in uric acid detection, and the uric acid detection with high sensitivity and anti-interference is achieved, and the preparation method is simple.
Patent Information
- Application Number
- CN202411809485.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-07
AI Technical Summary
The existing electrodes have poor reproducibility when detecting uric acid and are complex in the preparation process.
The electrode was prepared by self-assembly by mixing nanographite powder, glassy carbon microspheres, covalent organic frame material, ionic liquid and paraffin oil.
It realizes good reproducibility and anti-interference of uric acid detection, has high sensitivity, a detection limit of 0.5μM, and is simple in preparation and strong operability.
Smart Images

Figure CN119574656A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemical analysis methods, and specifically relates to a Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode and a preparation method thereof, and a method for detecting uric acid. Background Art
[0002] Uric acid (UA) is the final product of purine metabolism in the human body, and most of the uric acid produced in the human body is excreted through the kidneys. The process of uric acid excretion through the kidneys mainly includes four steps, namely glomerular filtration, tubular reabsorption and resecretion, and reabsorption after tubular secretion. When the body's purine metabolism is disordered or the kidneys are severely pathologically damaged, the uric acid content in the blood and urine will increase. In addition, excessive intake of foods with high purine content, such as meat, animal liver, fish and shrimp, will also cause an increase in uric acid content in the body, thereby causing hyperuricemia.
[0003] Studies have found that hyperuricemia is associated with a variety of diseases, such as cardiovascular disease, gout, and type 2 diabetes. In recent years, the number of patients with hyperuricemia has exploded. Therefore, the development of accurate, fast, and reliable uric acid analysis and detection technology is of great significance for clinical diagnosis and preventive health care, as well as research on physiological and pathological processes.
[0004] At present, the commonly used uric acid analysis methods mainly include the following technologies, such as enzymatic method, spectrophotometry, chromatography / mass spectrometry, electrochemical method, etc. Among them, the enzymatic method has good selectivity, but the disadvantage is that when determining uric acid, there is often interference from competitive enzyme inhibitors, and the cost of enzymes is high and the availability is low. In addition, the enzymatic method needs to be detected under specific conditions, and the results obtained cannot be judged by a unified standard, so there is no comparability; the spectrophotometric method is simple and fast in actual operation, but this method is not sensitive enough, and it is impossible to exclude the influence of interfering substances in the actual sample on the experiment, and the linear relationship is not high enough; the disadvantage of chromatography / mass spectrometry is that the sample needs to be processed in advance and relies on high-precision instruments; while the electrochemical analysis method can achieve rapid, accurate and reliable determination of uric acid, mainly due to its simple instrument structure and convenient operation. At the same time, this type of method also reflects the characteristics of rapid response, high sensitivity and the ability to achieve real-time detection. In the prior art, the Chinese invention patent with application number 202010707334.8 discloses an electrochemical method for detecting uric acid and urate oxidase and its application, specifically: first, glutathione (GSH) is used as a biological ligand, and silver ion Ag(I) is used as a metal node, and a biometal complex (GSH-Ag(I) complex) that has an electrocatalytic effect on H2O2 is synthesized based on the interaction between thiol-metal and metal-metal, and then the polymer is drop-coated on a GO-modified electrode to prepare a GSH-Ag(I) / GO / GCE electrode. The detection limit of this electrode for uric acid UA is 0.3μM. The above-mentioned electrode belongs to a modified glassy carbon electrode. Although this type of electrode has a lower detection limit, the modification process is relatively complicated, and after long-term use, the modified film of the glassy carbon electrode modified by layer-by-layer self-assembly or drop-coating method may fall off, and the reproducibility is poor. Summary of the invention
[0005] Based on this, the present invention provides a Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode to solve the technical problems of poor reproducibility and complex electrode preparation process in the prior art when detecting uric acid.
[0006] The present invention also provides a method for preparing the Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode, which has simple steps and strong operability.
[0007] The present invention also provides a method for detecting uric acid. Based on the above-mentioned Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode, the method has good sensitivity. Under the optimal experimental conditions, differential pulse voltammetry is used to quantitatively detect uric acid. The peak current value of uric acid on the electrode increases with the increase of its concentration. When the uric acid concentration is between 1 and 500 μM, the two have a good linear relationship, and the linear equation is I (μA) = 0.0696c (μM) - 0.3241 (r 2=0.9963), and when the signal-to-noise ratio was 3, the detection limit was 0.5 μM.
[0008] The technical solution of the present invention to solve the above technical problems is as follows:
[0009] A method for preparing a Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode comprises the following steps:
[0010] S10. The nano-graphite powder, glassy carbon microspheres, covalent organic framework material, ionic liquid and paraffin oil are mixed and ground to obtain a paste;
[0011] S20. Filling the paste into a container, heating and shaping, to obtain an electrode column;
[0012] S30. Polishing the surface of the electrode column to be smooth to obtain the Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode;
[0013] The covalent organic framework material is a covalent organic framework material formed by connecting 1,3,6,8-tetrakis(4-formaldehydephenyl)pyrene and benzidine.
[0014] Preferably, in the preparation method of the above-mentioned Py-PB-COF / glassy carbon microspheres-ionic liquid paste electrode, in each microliter of the paraffin oil, the added amount of the nano-graphite powder is 1 mg, the added amount of the glassy carbon microspheres is 1.25 mg, the added amount of the covalent organic framework material is 0.25 mg, and the added amount of the ionic liquid is 1.25 mg.
[0015] Preferably, in the method for preparing the above-mentioned Py-PB-COF / glassy carbon microspheres-ionic liquid paste electrode, the content of the covalent organic framework material in the nano-graphite powder, glassy carbon microspheres and covalent organic framework material is 6% to 12%.
[0016] Preferably, in the method for preparing the above-mentioned Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode, the ionic liquid is 1-octylpyridinium hexafluorophosphate ionic liquid.
[0017] A Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode is prepared by adopting the preparation method of the Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode.
[0018] An electrochemical sensor based on a Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode adopts the Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode as a working electrode.
[0019] A method for detecting uric acid comprises the following steps:
[0020] T10. Constructing an electrochemical sensor based on Py-PB-COF / glassy carbon microspheres-ionic liquid paste electrode as described in claim 7;
[0021] T20. constructing an electrolyte system, wherein the electrolyte system consists of a sample to be detected and a PBS buffer solution;
[0022] T30. Detect the concentration of uric acid.
[0023] Preferably, in the above-mentioned method for detecting uric acid, the concentration of the PBS buffer solution is 0.1 mol / L, and the pH value is 5 to 7.
[0024] Preferably, in the above-mentioned method for detecting uric acid, the "detecting the concentration of uric acid" comprises the following steps:
[0025] Differential pulse voltammetry was performed at room temperature in the scan range of 0.1 V to 0.6 V with accumulation at open circuit potential for 10 s.
[0026] Compared with the prior art, the present invention has at least the following advantages:
[0027] The present invention provides a Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode (Py-PB-COF / GCILE), which has good reproducibility, anti-interference and good sensitivity when applied to the detection of uric acid. The same electrode was used to measure uric acid six times in a row, and the calculated relative standard deviation RSD was 1.54%; six Py-PB-COF / GCILEs prepared by the same method were used to perform parallel detection of uric acid, and the RSD value of the peak current obtained was 0.92%. This shows that the Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode has good reproducibility in uric acid detection. For interfering substances, even at a level 100 times that of uric acid, common interfering substances such as Ca 2 +, Mg2+, Na+, Cl-, ascorbic acid and glucose, etc., have little effect on uric acid detection, and their relative standard deviations are all within ±5%, indicating that the Py-PB-COF / GCILE electrode exhibits good anti-interference performance in uric acid detection. Under the optimal experimental conditions, uric acid was quantitatively detected by square wave voltammetry, and the peak current value of uric acid on the electrode increased with the increase of its concentration. When the uric acid concentration is between 1 and 500 μM, the two have a good linear relationship, and the linear equation is I (μA) = 0.0696c (μM) - 0.3241 (r 2 =0.9963), when the signal-to-noise ratio was 3, the detection limit was 0.5 μM, indicating that it had a better sensitivity.
[0028] The present invention also provides a method for preparing a Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode, which only requires mixing and grinding nanographite powder, glassy carbon microspheres, covalent organic framework materials, ionic liquids and paraffin oil, and then self-assembling to prepare the Py-PB-COF / glassy carbon microspheres-ionic liquid paste electrode. The method is simple and easy to operate.
[0029] The present invention also provides a method for detecting uric acid, which is based on the above-mentioned Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode and has not only good reproducibility and anti-interference properties, but also good sensitivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 CV graphs of (a) GCPE, (b) Py-PB-COF / GCPE, and (c) Py-PB-COF / GCILE in 5 mM K3[Fe(CN)6] / K4[Fe(CN)6] probe solution containing 0.1 M KCl.
[0031] Figure 2 (A) Cyclic voltammograms of 5 mM K3[Fe(CN)6] / K4[Fe(CN)6] on GCPE at different scan rates. The scan rates from inside to outside are 50, 75, 100, 125, and 150 mV s -1 ; (B) Linear relationship between peak current and the square root of scan rate.
[0032] Figure 3 (A) Cyclic voltammograms of 5 mM K3[Fe(CN)6] / K4[Fe(CN)6] on Py-PB-COF / GCILE at different scan rates. The scan rates from inside to outside are 50, 75, 100, 125, and 150 mV s -1 ; (B) Linear relationship between peak current and the square root of scan rate.
[0033] Figure 4 Differential pulse voltammograms of 50 μM uric acid on (a) GCPE; (b) Py-PB-COF / GCPE; (c) Py-PB-COF / GCILE.
[0034] Figure 5 (A) CV graphs of 50 μM uric acid in Py-PB-COF / GCILE at different scan rates (the scan rates from inside to outside are 20, 40, 60, 80, 100, 125, 150, 175, 200 mV s -1 ); (B) Linear relationship between peak current and the square root of scan rate.
[0035] Figure 6(A) DPV diagram of 50 μM uric acid at different pH values (pH:ae are 4, 5, 6, 7, and 8, respectively); (B) relationship diagram between pH and peak current and peak potential of 50 μM uric acid.
[0036] Figure 7 The effect of different Py-PB-COF modification contents on the peak current of 50 μM uric acid.
[0037] Figure 8 This is the effect of enrichment potential on the peak current of 50 μM uric acid.
[0038] Fig. 9 The figure shows the effect of enrichment time on the peak current of 50 μM uric acid.
[0039] Fig.10 (A) DPV diagram of different concentrations of uric acid (from bottom to top: 0, 0.5, 1, 5, 10, 20, 50, 100, 200, 300, 400, 500 μM UA); (B) relationship between UA peak current and concentration. DETAILED DESCRIPTION
[0040] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present invention can be combined with each other. The technical solution of the present invention will be further described below in conjunction with the drawings of the embodiments of the present invention, and the present invention is not limited to the following specific implementation methods.
[0041] It should be understood that the same or similar reference numerals in the drawings of the embodiments correspond to the same or similar components. In the description of the present invention, it should be understood that if there are terms such as "upper", "lower", "front", "rear", "left", "right", "top", "bottom" and the like indicating an orientation or positional relationship, it is based on the orientation or positional relationship shown in the drawings, which is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation. Therefore, the terms describing the positional relationship in the drawings are only used for illustrative purposes and cannot be understood as a limitation on this patent. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to specific circumstances.
[0042] In one specific embodiment of the present invention, a method for preparing a Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode comprises the following steps:
[0043] S10. The nano-graphite powder, glassy carbon microspheres, covalent organic framework material, ionic liquid and paraffin oil are mixed and ground to obtain a paste;
[0044] Specifically, nano-graphite powder, glassy carbon microspheres, covalent organic framework materials, ionic liquids and paraffin oil are weighed respectively and ground evenly in an agate mortar to obtain a paste.
[0045] Covalent Organic Framework (COFs) is a porous crystalline material composed of light elements such as C, H, N, and O connected by covalent bonds. Due to its regular and orderly pore structure, large specific surface area, good stability, and designable structure, it has been widely used in adsorption, energy storage, catalysis and other fields, and also shows good application prospects in electrochemical sensing. The covalent organic framework material in this scheme is a covalent organic framework material Py-PB-COF formed by connecting 1,3,6,8-tetrakis(4-formaldehydephenyl)pyrene and benzidine. The CAS number of 1,3,6,8-tetrakis(4-formaldehydephenyl)pyrene is 1415238-25-3, and the molecular formula is C 44 H 26 O4, molecular weight is 618.67; CAS number of benzidine is 92-87-5, molecular formula is C 12 H 12 N2, molecular weight is 184.24. Py-PB-COF mainly plays the role of a modifier in the present application. When detecting uric acid, the content of Py-PB-COF is gradually changed. When the modification amount of Py-PB-COF increases from 2% to 10%, the oxidation peak current of uric acid on the electrode increases in a step-like manner. At 6% to 12%, the oxidation peak current of uric acid is in a higher numerical range and reaches a maximum value at 10%. The possible reason is that the appropriate amount of Py-PB-COF increases the surface area of the modified electrode. Therefore, preferably, the content of Py-PB-COF in the nano-graphite powder, glassy carbon microspheres, and Py-PB-COF is 6% to 12%, and the optimal amount is 10%.
[0046] Preferably, in each microliter of the paraffin oil, the amount of the nanographite powder added is 1 mg, the amount of the glassy carbon microspheres added is 1.25 mg, the amount of the covalent organic framework material added is 0.25 mg, and the amount of the ionic liquid added is 1.25 mg. It should be noted that the amount of the nanographite powder added, the amount of the glassy carbon microspheres added, the amount of the covalent organic framework material added, and the amount of the ionic liquid added are not a numerical point, but there is a certain floating numerical range, and the numerical floating range is not greater than 15%.
[0047] Preferably, the ionic liquid is 1-octylpyridinium hexafluorophosphate ionic liquid, which in the present embodiment acts as a modifier on the one hand, and acts as a binder together with paraffin oil on the other hand.
[0048] S20. Filling the paste into a container, heating and shaping, to obtain an electrode column;
[0049] S30. Polishing the surface of the electrode column to be smooth to obtain the Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode;
[0050] Specifically, the paste was squeezed into the electrode tube and pressed tightly, the electrode tube was heated with a hair dryer until the ionic liquid melted, and then the electrode was placed on weighing paper and polished to be smooth to obtain the Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode (Py-PB-COF / GCILE).
[0051] In a specific embodiment of the present invention, a Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode is prepared by the above-mentioned preparation method of the Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode.
[0052] In another embodiment of the present invention, an electrochemical sensor based on Py-PB-COF / glassy carbon microspheres-ionic liquid paste electrode uses the above-mentioned Py-PB-COF / glassy carbon microspheres-ionic liquid paste electrode as a working electrode.
[0053] In another embodiment of the present invention, a method for detecting uric acid comprises the following steps:
[0054] T10. Constructing an electrochemical sensor based on Py-PB-COF / glassy carbon microspheres-ionic liquid paste electrode as described in claim 7;
[0055] For example, an electrochemical sensor is constructed using the Py-PB-COF / GCILE prepared by the above method as the working electrode, the Pt electrode as the auxiliary electrode, and the saturated calomel electrode as the reference electrode.
[0056] T20. constructing an electrolyte system, wherein the electrolyte system consists of a sample to be detected and a PBS buffer solution;
[0057] A PBS buffer solution with a concentration of 0.1 mol / L and a pH value of 5 to 7 is selected as the main electrolyte of the electrolyte system, and then an appropriate amount of the sample solution to be detected containing uric acid is added to the PBS buffer solution to obtain the electrolyte system.
[0058] T30. Detect the concentration of uric acid.
[0059] Based on the electrochemical sensor and the electrolyte system, differential pulse voltammetry was used at room temperature with a scanning range of 0.1 V to 0.6 V and an open circuit potential enrichment of 10 s to obtain the voltammetric curve of uric acid. The concentration of uric acid was directly obtained based on the linear relationship between the oxidation peak current and the concentration of uric acid.
[0060] It is worth noting that the Py-PB-COF / GCILE provided by the present invention has good reproducibility, anti-interference and good sensitivity when applied to the detection of uric acid. The same electrode was used to measure uric acid six times in a row, and the calculated relative standard deviation RSD was 1.54%; six Py-PB-COF / GCILE prepared by the same method were used for parallel detection of uric acid, and the RSD value of the peak current obtained was 0.92%. It shows that the Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode has good reproducibility in uric acid detection. For interfering substances, even at a level of 100 times the concentration of uric acid, common interfering substances such as Ca2+, Mg2+, Na+, Cl-, ascorbic acid and glucose have little effect on uric acid detection, and their relative standard deviations are all within ±5%, indicating that the Py-PB-COF / GCILE electrode exhibits good anti-interference performance in uric acid detection. Under the optimal experimental conditions, uric acid was quantitatively detected by square wave voltammetry. The peak current value of uric acid on the electrode increased with the increase of its concentration. When the uric acid concentration was between 1 and 500 μM, the two had a good linear relationship, and the linear equation was I (μA) = 0.0696c (μM) - 0.3241 (r 2 =0.9963), and when the signal-to-noise ratio is 3, the detection limit is 0.5 μM, indicating that its sensitivity is relatively good. The preparation method provided by the present invention only requires mixing and grinding nanographite powder, glassy carbon microspheres, Py-PB-COF, ionic liquid and paraffin oil, and then self-assembling to prepare the Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode, and the method is simple and easy to operate.
[0061] The technical solution and technical effects of the present invention are further illustrated below through a specific experimental process.
[0062] 1. Experimental part
[0063] 1.1 Materials and reagents
[0064] Table 1 Experimental reagents and manufacturers
[0065]
[0066]
[0067] Different pH buffer solutions (PBS) were prepared from Na2HPO4 and KH2PO4; the mixed probe solution was prepared from K3[Fe(CN)6], KCl, and K4Fe(CN)6; uric acid was dissolved with 0.1M NaOH solution, and ultrapure water was used in the experiment.
[0068] 1.2 Instruments and Equipment
[0069] Table 2 Experimental equipment models and manufacturers
[0070] name model factory Electrochemical workstation CHI660E Shanghai Chenhua Instrument Co., Ltd. Glassy Carbon Electrode CHI104 Shanghai Chenhua Instrument Co., Ltd. Platinum wire electrode CHI115 Shanghai Chenhua Instrument Co., Ltd. Saturated calomel electrode CHI150 Shanghai Chenhua Instrument Co., Ltd. Electronic balance AL204 Mettler Toledo Technologies (China) Co., Ltd. Magnetic stirrer IKAKMO2 Aika (Guangzhou) Instrument Equipment Co., Ltd.
[0071] 1.3 Electrode preparation
[0072] 0.02g of nanographite powder, 0.025g of glassy carbon microspheres, 0.005g of Py-PB-COF, 0.025g of 1-octylpyridinium hexafluorophosphate and 20μL of paraffin oil were mixed and put into a grinder and ground until the components were fully mixed and ground evenly. 1 / 3 was squeezed into the electrode tube and pressed tightly. The electrode tube was heated with a hair dryer until the ionic liquid melted, and then the electrode was placed on a weighing paper and polished to obtain a Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode (Py-PB-COF / GCILE). The glassy carbon microsphere paste electrode (GCPE) and Py-PB-COF / glassy carbon microsphere paste electrode (Py-PB-COF / GCPE) were prepared by the same method to compare the performance parameters of different electrodes later.
[0073] 1.4 Experimental methods
[0074] Use a pipette to draw 5mL of pH=6 buffer into a clean small beaker, add a stirrer, and then insert the prepared Py-PB-COF / GCILE into the beaker together with the Pt wire electrode and the saturated calomel electrode. Use differential pulse voltammetry (DPV) to measure the blank solution first, then add a certain concentration of uric acid and enrich it under open circuit potential conditions for 10s before detection. In the scanning potential range of 0.1V to 0.6V, measure the electrochemical signal of uric acid on the electrode to study its electrochemical behavior on the modified electrode.
[0075] 2. Results and Discussion
[0076] 2.1 Electrochemical characterization of modified electrodes
[0077] Figure 1 The CV graphs of GCPE, Py-PB-COF / GCPE, and Py-PB-COF / GCILE in 5 mM mixed probe solution are shown in Figure 2. 5 mL of mixed probe solution was pipetted into a small beaker, and the experimental conditions were set. At the open circuit potential, the measurement potential range was -0.2 V to 0.6 V, and the instrument scanning speed was 50 mV s -1 The CV method was used to characterize the three electrodes: GCPE, Py-PB-COF / GCPE, and Py-PB-COF / GCILE, and then the data measured by the three electrodes were superimposed and plotted.
[0078] like Figure 1As shown in the figure, since Py-PB-COF is modified on the glassy carbon microsphere paste electrode, the effective surface area of the modified electrode is increased, which causes more substrates to be adsorbed on the electrode surface. The peak current of the mixed probe on Py-PB-COF / GCPE (curve b) is significantly higher than that on GCPE (curve a). In addition, it can be found that the peak current on Py-PB-COF / GCILE is much larger than that on the first two electrodes, the oxidation peak current increases significantly, and the peak potential difference decreases significantly, indicating that the Py-PB-COF / ionic liquid complex plays a huge role, has good conductivity and adsorption capacity, and can improve the performance of the modified electrode.
[0079] 2.2 Surface area study
[0080] Figure 2 A. Figure 3 A is the CV graph of GCPE and Py-PB-COF / GCILE at different scan rates in the mixed probe solution. As can be seen from the figure, the scan rate is positively correlated with the peak current. Further research found that the peak current of the electrode is not linearly related to the scan rate, but linearly related to the square root of the scan rate, such as Figure 2 B. Figure 3 As shown in B, the linear equations are:
[0081] GCPE: I(μA)=56.6282v 1 / 2 (V 1 / 2 s -1 / 2 )+26.3418(r 2 =0.9945);
[0082] Py-PB-COF / GCILE: I(μA)=275.4077v 1 / 2 (V 1 / 2 s -1 / 2 )+28.0571(r 2 =0.9972);
[0083] Since the reaction of the hybrid probe on the modified electrode is a reversible reaction, its oxidation peak current (Ipa) increases with the square root of the scan rate (υ 1 / 2 ) conforms to the Randles-Sevcik formula:
[0084] Ipa=(2.69×10 5 ) 3 / 2 AC0D R 1 / 2 υ 1 / 2 (1)
[0085] Where Ipa, n and C0 represent the anodic peak current, the number of electron transfers and the concentration of K3[Fe(CN)6] / K4[Fe(CN)6], respectively; DR and υ represent the diffusion coefficient and the scan rate, respectively; and A is the effective surface area of the electrode.
[0086] According to Ipa~υ 1 / 2 From the relationship, (2.69×10 5 ) 3 / 2 AC0D R 1 / 2 is equal to the slope of the linear equation, from which we can calculate that the active surface areas A of GCPE and Py-PB-COF / GCILE are 0.017 cm 2 、0.082cm 2 The results showed that the effective surface area of Py-PB-COF / GCILE was about 5 times that of GCPE, indicating that the Py-PB-COF / IL composite material can significantly increase the effective surface area of the modified electrode, improve the adsorption capacity of the modified electrode, provide more binding sites, and promote electron transfer, thereby amplifying the response signal.
[0087] 2.3 Study on the electrochemical behavior of uric acid on electrodes modified with different modifiers
[0088] like Figure 4 As shown in the figure, a smaller uric acid oxidation peak can be observed at 0.344V on GCPE (curve a), and its oxidation peak current is about 0.764μA. When Py-PB-COF is modified to the electrode surface, the peak current on Py-PB-COF / GCPE (curve b) increases significantly (about 1.730μA), and the peak potential shifts negatively (about 0.332V), indicating that Py-PB-COF can improve the electrocatalytic activity of the modified electrode. At 0.300V, a sharp uric acid oxidation peak appears on Py-PB-COF / GCILE (curve c), and its oxidation peak current increases significantly to 7.736μA, which is about 10 times the peak current on GCPE. At the same time, its peak potential shifts further negatively. This is because the Py-PB-COF / ionic liquid complex can provide more active sites, increase the loading amount of uric acid on the modified electrode, and promote the electron transfer of uric acid between the solution and the electrode surface.
[0089] 2.4 Effect of scanning speed
[0090] Figure 5 A CV curves of 50 μM uric acid on Py-PB-COF / GCILE at different scan rates, ranging from 20 to 200 mV s -1 As can be seen from the figure, uric acid presents an irreversible oxidation peak in the CV graph, and the oxidation peak current of uric acid increases with the increase of the scanning rate. Figure 5 B further reveals that in the range of 20 to 200 mV s -1 Within the scanning rate range, there is a linear relationship between the oxidation peak current of uric acid and the square root of the scanning rate (v1 / 2), and it conforms to the following linear equation: I (μA) = 0.5521v 1 / 2 (mV 1 / 2 s -1 / 2 )+1.0569(r 2 =0.9994), which shows that the electrochemical reaction of uric acid on Py-PB-COF / GCILE is a diffusion-controlled process.
[0091] 2.5 Optimization of detection conditions
[0092] 2.5.1 Effect of solution pH
[0093] In this study, the pH value of the buffer solution was changed to observe its effect on the electrode detection of uric acid. Figure 6 A shows the DPV graph of uric acid obtained by differential pulse voltammetry in buffer solutions with different pH values. The results show that as the pH value increases, the peak potential of uric acid gradually shifts to a negative potential. Figure 6 B is the relationship between pH and the peak current and peak potential of 50 μM uric acid. As can be seen from the figure, there is a linear relationship between the pH value of the buffer solution and the peak potential of uric acid, which conforms to the following linear equation: E(V) = -0.0584pH-0.6171(r 2 =0.9831). The slope of the equation is -58.4 mV pH -1 Close to the theoretical value (-59mVpH -1 ), indicating that the number of protons and electrons involved in the electrode reaction is equal. When the pH value of the buffer solution PBS increases from 4 to 6, the peak current of uric acid gradually increases; when the pH value changes from 6 to 8, the peak current of uric acid gradually decreases, and the peak current reaches the maximum at pH = 6. In order to maximize the sensitivity of the modified electrode to detect uric acid, the subsequent experiments will use PBS buffer with pH = 6 for measurement.
[0094] 2.5.2 Effect of Py-PB-COF content
[0095] This study investigated the effect of Py-PB-COF content on the measurement of uric acid concentration. Figure 7As shown in the figure, the Py-PB-COF content (the content of Py-PB-COF in nanographite powder, glassy carbon microspheres, and Py-PB-COF) was gradually changed, and the addition amount of other raw materials remained unchanged. When the modification amount of Py-PB-COF increased from 2% to 10%, the oxidation peak current of uric acid on the electrode increased in a step-like manner and reached a maximum value at 10%. The possible reason is that the appropriate amount of Py-PB-COF increases the surface area of the modified electrode and enhances the adsorption capacity of uric acid, thereby improving the current response. However, in the process of increasing the Py-PB-COF content from 10% to 15%, the oxidation peak current of uric acid began to decrease. This may be because the excessive Py-PB-COF caused the background current to increase, which in turn affected the current response of uric acid on the modified electrode. Therefore, this experiment determined the modification amount of Py-PB-COF to be 10%.
[0096] 2.5.3 Enrichment potential and enrichment time
[0097] By changing the enrichment potential and enrichment time, their effects on uric acid determination were observed. Figure 8 To investigate the effect of the enrichment potential on the uric acid peak current, the results showed that when the enrichment potential varied between -0.4V and 0.4V, the uric acid peak current first increased and then decreased, with a maximum value at -0.2V. When the enrichment potential was 0.2V, the peak current increased but did not reach the maximum value, and then the peak current continued to decrease. During the experiment, we noticed that the peak current value measured under open circuit potential was higher than the peak current value when the potential was applied. This phenomenon indicates that it is more advantageous to perform uric acid detection at open circuit potential. Therefore, we decided to use open circuit potential as the condition for uric acid detection.
[0098] Fig. 9 The effect of enrichment time on the peak current of uric acid was discussed. As shown in the figure, when the enrichment time was 10s, the enrichment of uric acid on the modified electrode reached equilibrium and obtained satisfactory detection results, indicating that the modified electrode responded quickly to uric acid and could detect uric acid in a very short time. When the enrichment time exceeded 30s, the peak current decreased, indicating that a longer time would affect the detection of uric acid. Therefore, we chose the optimal enrichment time as 10s.
[0099] 2.6 Standard curve
[0100] Differential pulse voltammetry was used to detect different concentrations of uric acid using the constructed Py-PB-COF / GCILE. Fig.10 A shows that the peak current value of uric acid on the electrode increases with the increase of its concentration. Fig.10 B shows that when the uric acid concentration is between 1 and 500 μM, the two have a good linear relationship, and the linear equation is I (μA) = 0.0696c (μM) - 0.3241 (r2 =0.9963). When the signal-to-noise ratio was 3, the detection limit was 0.5 μM.
[0101] 2.7 Reproducibility study
[0102] This study evaluated the reproducibility of Py-PB-COF / GCILE in the detection of uric acid. By applying the established detection method, 50μM uric acid was measured six times in succession using the same electrode, and the calculated relative standard deviation (RSD) was 1.54%. In addition, six Py-PB-COF / GCILE prepared by the same method were used for parallel detection of uric acid, and the RSD value of the peak current obtained was 0.92%. The results show that Py-PB-COF / GCILE has good reproducibility in uric acid detection.
[0103] 2.8 Interference Study
[0104] This study evaluated the anti-interference properties of Py-PB-COF / GCILE in uric acid detection. The experimental results show that even at 100 times the concentration of uric acid, common interferences such as Ca2+, Mg2+, Na+, Cl-, ascorbic acid and glucose have little effect on uric acid detection, and their relative standard deviations are all within ±5%. This shows that the Py-PB-COF / GCILE electrode exhibits good anti-interference performance in uric acid detection.
[0105] 2.9 Sample testing
[0106] In order to verify the feasibility of Py-PB-COF / GCILE in detecting uric acid in actual samples, we applied this method to detect the content of uric acid in the urine of volunteers. The urine sample processing method is as follows: the urine sample is diluted 10 times with 0.1MpH 6.0 PBS buffer solution for detection. The test results show that the uric acid content detected in sample 1 is 1183μM, and the uric acid content detected in sample 2 is 1028μM. The results of the spike recovery experiment are shown in Table 3, and the spike recovery rate is 95.28% to 99.01%. The results show that Py-PB-COF / GCILE can be used for the analysis of uric acid content in actual sample urine samples.
[0107] Table 3 Uric acid in samples determined by Py-PB-COF / GCILE (n=3 a )
[0108] Urine sample 1 Urine sample 2 Detection value / μM 118.87 102.77 Spiked amount / μM 100.00 100.00 Detection amount after spike addition / μM 217.88 198.04 Recovery rate / % 99.01 95.28 Relative standard deviation / % 5.82 0.36
[0109] a The sample was measured three times and the average value was taken
[0110] 3 Conclusion
[0111] From the above experimental process, it can be seen that the present invention uses Py-PB-COF to modify the glassy carbon microsphere-ionic liquid paste electrode to establish a new method for simple and rapid detection of uric acid. Compared with other electrodes, the response current of uric acid on the Py-PB-COF modified electrode is significantly increased, indicating that the performance of the modified electrode has been effectively improved. Scan rate studies have shown that the electrochemical reaction of uric acid on Py-PB-COF / GCILE is a diffusion-controlled process. Under optimized conditions, that is, using 0.1M PBS (pH=6) as a buffer, a Py-PB-COF content of 10%, and open circuit enrichment for 10s, the sensor exhibits the best response performance. Under these optimal conditions, the Py-PB-COF / GCILE electrode exhibited excellent reproducibility (the relative standard deviation RSD calculated for six consecutive measurements of uric acid using the same electrode was 1.54%; the RSD value of the peak current obtained for parallel detection of uric acid using six Py-PB-COF / GCILE prepared by the same method was 0.92%), a wide linear range (1-500 μM) and a low detection limit (0.5 μM). In addition, this method is simple, rapid and has strong anti-interference ability, and can be applied to the detection of uric acid in actual samples.
[0112] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode, characterized in that: The following steps are involved: S10. The nano-graphite powder, glassy carbon microspheres, covalent organic framework material, ionic liquid and paraffin oil are mixed and ground to obtain a paste; S20. Filling the paste into a container, heating and shaping, to obtain an electrode column; S30. Polishing the surface of the electrode column to be smooth to obtain the Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode; The covalent organic framework material is a covalent organic framework material formed by connecting 1,3,6,8-tetrakis(4-formaldehydephenyl)pyrene and benzidine.
2. The method for preparing the Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode according to claim 1, characterized in that: In each microliter of the paraffin oil, the added amount of the nanographite powder is 1 mg, the added amount of the glassy carbon microspheres is 1.25 mg, the added amount of the covalent organic framework material is 0.25 mg, and the added amount of the ionic liquid is 1.25 mg.
3. The method for preparing the Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode according to claim 1, characterized in that: Among the nano graphite powder, glassy carbon microspheres and covalent organic framework materials, the content of the covalent organic framework material is 6% to 12%.
4. The method for preparing the Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode according to claim 1, characterized in that: The ionic liquid is 1-octylpyridinium hexafluorophosphate ionic liquid.
5. A Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode, characterized in that: The electrode is prepared by the method for preparing the Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode as described in any one of claims 1 to 4.
6. An electrochemical sensor based on Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode, characterized in that: The Py-PB-COF / glassy carbon microsphere-ionic liquid paste electrode as claimed in claim 5 is used as the working electrode.
7. A method for detecting uric acid, characterized in that: The following steps are involved: T10. Constructing an electrochemical sensor based on Py-PB-COF / glassy carbon microspheres-ionic liquid paste electrode as described in claim 6; T20. constructing an electrolyte system, wherein the electrolyte system consists of a sample to be detected and a PBS buffer solution; T30. Detect the concentration of uric acid.
8. The method for detecting uric acid according to claim 7, characterized in that: The concentration of the PBS buffer solution is 0.1 mol / L, and the pH value is 5 to 7.
9. The method for detecting uric acid according to claim 7, characterized in that: The "detection of uric acid concentration" comprises the following steps: Differential pulse voltammetry was performed at room temperature in the scan range of 0.1 V to 0.6 V with accumulation at open circuit potential for 10 s.
Citation Information
Patent Citations
An electrochemical method for detecting uric acid and uric acid oxidase and its application
CN111879836B